JAPAN AND JAPONISME IN LATE NINETEENTH CENTURY LITERATURE - FUKUZAWA, NAOMI CHARLOTTE ([S.l.] : ROUTLEDGE, 2024)
This book examines the transnational phenomenon of Japonisme in the exoticist and autoexoticist literature of the late nineteenth century. Focusing on the way in which reciprocal processes of transcultural acquisition - by Japan and from Japan - were portrayed in the medium of literature, the book illustrates how literary Japonisme and the wider processes whereby Japan, with its alien exotic culture and unique refined aestheticism, was absorbing Western civilization in its own way in the late nineteenth century at the same time as the phenomenon of Japonisme was occurring in Western fine arts, which were inspired by traditional Japanese artistic practices. Specifically, the book focuses on the literary works of Lafcadio Hearn and Pierre Loti, who travelled from France and America, respectively, to Japan, and Mori gai and Natsume Sseki, who in turn went, respectively, to Germany and England from Japan. Exploring the eclectic hybridity of Japan's modernization during the late nineteenth century, this book will appeal to students and scholars of Japanese Studies, Postcolonial Studies and Comparative Literature.
Keywords: Japonism; Japanese literature -- 19th century -- History and criticism; Japanese literature -- Western influences; French literature -- Japanese influences; American literature -- Japanese influences; LITERARY CRITICISM / Asian / Japanese; SOCIAL SCIENCE / Research